PENGARUH PENAMBAHAN MINYAK GORENG HEWANI PADA MINYAK SAWIT TERHADAP PERUBAHAN SUDUT POLARISASI - Kaltsum, Ummi; Idrus, Hadiyati; Firdausi, K. Sofjan (BERKALA FISIKA, 2014)
The use of animal oil for various purposes by the people has inspired this study. The purpose of the study was to distinguish the mixture of cooking oil palm and variety of animal oil (chicken oil, beef oil, and pork oil). The composition of the mixture of palm oil and animal oil is 3:1 mL, respectively. The light source used were He-Ne laser of 1 mW (Î» = 633 nm) and IR lamp of 250 watt (Î» = 750-800 nm). Measurements were made based on changes in the natural polarization angle (0 kV) and electrooptics (6 kV). The result showed that the natural polarization angle changes and electrooptics ofÂ mixture of palm oil and animal oil greater than pure palm oil, both at He-Ne laser and IR light. This is consistent with the results of the titration test, peroxide value and free fatty acids (FFA) oil mixture was greater than pure palm oil. Change in the polarization angle represents the presence of saturated fatty acids. Animal oils have saturated fatty acid content greater than palm oil, so the polarization angle changes of oil mixture is greater than polarization angle changes of pure palm oil. Keywords: animal frying oil, palm oil, polarization angle